Worlds Enough : The Invention of Realism in the Victorian Novel - Freedgood, Elaine (Book collections on Project MUSE., 2019)
"A short, provocative book that challenges basic assumptions about Victorian fiction. Now praised for its realism and formal coherence, the Victorian novel was not always great, or even good, in the eyes of its critics. As Elaine Freedgood reveals in Worlds Enough, it was only in the late 1970s that literary critics constructed a prestigious version of British realism, erasing more than a century of controversy about the value of Victorian fiction. Examining criticism of Victorian novels since the 1850s, Freedgood demonstrates that while they were praised for their ability to bring certain social truths to fictional life, these novels were also criticized for their formal failures and compared unfavorably to their French and German counterparts. She analyzes the characteristics of realism--denotation, omniscience, paratext, reference, and ontology--and the politics inherent in them, arguing that if critics displaced the nineteenth-century realist novel as the standard by which others are judged, literary history might be richer. It would allow peripheral literatures and the neglected wisdom of their critics to come fully into view. She concludes by questioning the aesthetic racism built into prevailing ideas about the centrality of realism in the novel, and how those ideas have affected debates about world literature. By re-examining the critical reception of the Victorian novel, Worlds Enough suggests how we can rethink our practices and perceptions about books we think we know."